2016
DOI: 10.1111/1747-0080.12292
|View full text |Cite
|
Sign up to set email alerts
|

Estimated portion size versus actual intake of eight commonly consumed foods by healthy adults

Abstract: Aim This study aimed to examine the accuracy of the estimated portion size (EPS) of foods required to reach satiation, and how food characteristics influence food portion estimation in healthy adults. Methods This was a randomised, cross‐over feeding trial with eight test sessions. The visual, olfactory and rheological characteristics of common foods were manipulated. Participants determined the portion sizes of eight test foods that need to be consumed to reach satiation, which were then compared with the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…A second concern is that an individual's ideal portion size may not always be representative of their actual consumption. Research generally supports estimates of ideal portion size as a strong predictor of actual food intake (Nguyen, Chern, & Tan, 2016;Wilkinson et al, 2012). However, one study reported poor congruence between measures that indicate disinhibition and portion size during expected and actual eating sessions, e.g.…”
Section: Interim Discussionmentioning
confidence: 99%
“…A second concern is that an individual's ideal portion size may not always be representative of their actual consumption. Research generally supports estimates of ideal portion size as a strong predictor of actual food intake (Nguyen, Chern, & Tan, 2016;Wilkinson et al, 2012). However, one study reported poor congruence between measures that indicate disinhibition and portion size during expected and actual eating sessions, e.g.…”
Section: Interim Discussionmentioning
confidence: 99%
“…After the total 90 min calorimeter measurements, participants completed a meal challenge, where they were provided with 300 ml of plain water and bread with jam (sweet) and ham (savoury) toppings. Participants were asked to eat until they were comfortably full, which was defined as a fullness level where participants will not be eating other foods in the subsequent 3 to 4 h [20,21]. Appetite sensations were assessed pre- and post-consumption of test foods, as well as pre- and post-meal challenge, and sweetness levels of test foods were assessed immediately after ingestion of test foods.…”
Section: Methodsmentioning
confidence: 99%
“…Four articles in this issue examined factors that can influence food choice and consumption, such as food literacy and labelling, portion size estimation and, at a higher level, the food regulation setting . The paper by Wilson et al .…”
Section: Current Journal Issuementioning
confidence: 99%
“…Four articles in this issue examined factors that can influence food choice and consumption, such as food literacy and labelling, 21,22 portion size estimation 23 and, at a higher level, the food regulation setting. 24 The paper by Wilson et al 24 aimed to identify how food regulators can facilitate their response to food incidents to ensure that consumer trust is maintained and that food and nutrient intakes are not adversely affected.…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation